Experimental tests of public support for disability policy - Shane Timmons; Eamonn Carroll; Frances McGinnity (The Economic and Social Research Institute (ESRI), 2023)
Despite the right of disabled people to full social and economic inclusion, many face multiple day-to-day and systemic challenges. These include but are not limited to additional expenses, access to housing, and everyday accessibility difficulties. Surveys show the general public hold positive attitudes towards policies that seek to enable disabled people to overcome these challenges, but standard survey methods are susceptible to response biases that may overestimate this support. This study aimed to test whether two such biases influence support for disability policy in Ireland: social desirability bias (i.e. the tendency for survey respondents to alter their responses in order to present themselves in a positive light); and inattention to the implications of policy support (e.g. that welfare policies require funding). Together the survey experiments covered a range of policy issues and types of disability, as identified in previous research and in consultation with the disability advisory group for the project.
Keywords: 330; Behindertenpolitik; Öffentliche Meinung; Irland